Nitrogen-rich green leaves of papaya and Coccinia grandis as precursors of activated carbon and their electrochemical properties - Paweena Dulyaseree; Masatsugu Fujishige; Ichiro Yoshida; Yumiko Toya; Yasuo Banba; Yu-suke Tanaka; Takaaki Aoyama; Mayuree Phonyiem; Winadda Wongwiriyapan; Kenji Takeuchi; Morinobu Endo (My University, 2017)
Activated nitrogen-rich green leaves of papaya and Coccinia grandis show high surface area without the detriment of the electric conductivity.
Keywords: Carbon fibers; Conducting polymers and applications